Analysis of production trends in the major root and tuber crops in Nigeria, 1961-2005 - Ojiako, I.A.; Asumugha, G.N.; Ezedinma, C.I.; Uzokwe, Veronica N.E. (2007)
This study investigated the production trends in the principal root and tuber crops in Nigeria during the 1961-2005 periods and contrasted the performance of the crops at certain stages of economic and political reforms in the country. It was found that output of all roots and tubers rose tremendously during the era of the structural adjustment (SAP) introduced in 1986 and remained high during the post-SAP democratic era. Prior to SAP, production was generally low with sweetpotato, yam and cocoyam recording negative growth rates. However, the highest growth was achieved for all products during SAP. Except for cocoyam, growth rates for all other crops that ranged from 4.17% for cassava to 22.89% for ginger exceeded the estimated annual population growth rate of 3.00%. The implication is that the SAP liberalization policy and the introduction and dissemination of high-yielding and disease resistant crops' varieties impacted positively on output of roots and tubers in Nigeria. The lower growth rates found for all crops during the post-SAP relative to the SAP period resulted because the monies released as democratic dividends for the expansion of the rural economy were misapplied into nonfarm livelihood activities for higher returns. The study observed that the low returns to investments in agriculture have made the sector less attractive and suggested introduction of policies capable of promoting marketing and storage of agricultural produce.